DETERMINANTS ADVERTISING TAX REVENUE IN SEMARANG CITY - Tiska Febriyani, 09.05.52.0034; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2013)
Tax is one of the main sources of state revenue, because the roles of the tax sector are enormous, especially to support the successful development of the national, provincial and district /city. One component of Advertising Tax is the local tax. Advertising Tax is one kind of regional tax revenue sources that are important to Semarang city and surrounding areas. This was evident during the years 2002-2011 Advertising Tax revenues have increased. The purpose of this study was to analyze the effect of the total population, the number of industries and inflation on tax revenues advertising in Semarang. The sample in this study is the realization of advertising tax reports, population, number of industries, and the inflation of Semarang and surrounding areas years 2002-2011. Sampling technique is used to determine the sample is using random sampling (sampling not replacement) samples are taken randomly.Sampling not replacement is a sampling technique in which samples were not selected returned to the population before the return of the sample is then performed. Results from this study are expected to provide input for the benefit and Local Government of Semarang City especially the Department Street Lighting and Advertising Management (PJPR). The statistical tool used is multiple linear regression.The results of the regression analysis showed that the population has a significant positive effect, while the number of industrial and inflation has a significant negative effect on tax revenues advertisement.Keywords: Advertising Tax, Total Population, Total Industry, Inflation.